Volume 2: Dynamics, Vibration and Control; Energy; Fluids Engineering; Micro and Nano Manufacturing 2014
DOI: 10.1115/esda2014-20108
|View full text |Cite
|
Sign up to set email alerts
|

First Steps in the Design and Construction of the Ocean Grazer

Abstract: A novel wave energy converter, termed the Ocean Grazer, designed to extract energy from waves of varying profiles and energy contents has recently been proposed by the University of Groningen. The authors have performed preliminary modeling work to predict the behavior of the converter’s power take-off system, and constructed a proof-of-concept prototype to validate basic model predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Its adaptability to different types of waves is one of the main strengths of this WEC, which requires several buoys in a column to extract most of the wave energy in a sequential manner. The WEC is part of the Ocean Grazer, which is a novel ocean energy collection and storage device, designed to extract and store multiple forms of ocean energy (Vakis, Meijer, & Prins 2014, van Rooij, Meijer, Prins, & Vakis 2015, Vakis & Anagnostopoulos 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Its adaptability to different types of waves is one of the main strengths of this WEC, which requires several buoys in a column to extract most of the wave energy in a sequential manner. The WEC is part of the Ocean Grazer, which is a novel ocean energy collection and storage device, designed to extract and store multiple forms of ocean energy (Vakis, Meijer, & Prins 2014, van Rooij, Meijer, Prins, & Vakis 2015, Vakis & Anagnostopoulos 2016.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of concepts has been proposed to extract the ocean wave energy, ranging from oscillating water columns (OWCs), Attenuators, terminators, and point absorbers-type of device. Some examples are the Spar-buoy Oscillating Water Column [25], the Pelamis WEC [26], the Wave Dragon WEC [27], and the Ocean Grazer WEC [28,29]. Different approaches to harvest available ocean wave energy have been proposed.…”
Section: Energy-based Modeling Of the Ocean Grazer Wave Energy Convertermentioning
confidence: 99%
“…Although the key idea behind the concept of OG-WEC's MPP-PTO is clear, the set of switching algorithms to determine which pump to be activated for which wave conditions needs to be established. To achieve this, several attempts to model the behavior of the OG-WEC has been developed [1,28,29,33]. In particular, [1] showed that proper switching mechanism of the MPP-PTO concept allows the OG-WEC to optimally extract potential energy from the incoming waves.…”
Section: Energy-based Modeling Of the Ocean Grazer Wave Energy Convertermentioning
confidence: 99%
“…No cenário nacional existem pesquisas sendo realizadas por um grupo da Universidade Federal do Rio Grande (FURG) sobre essa modalidade, com foco na avaliação do recurso (Souza, 2014;Souza e Marques, 2016 Mundialmente, a geração de eletricidade a partir das ondas, por vezes chamada de energia ondomotriz, já apresenta algumas décadas de pesquisa. Existe uma grande diversidade de tecnologias de extração, algumas já instaladas e em fase pré-comercial de desenvolvimento (Thorpe, 1999;Falcão, 2010;Vakis et al, 2014;Uihlein e Magagna, 2016 (Cornett, 2006;Lenee-Bluhm et al, 2011; O potencial de aproveitamento de energia das ondas no Brasil já foi estudado, sobretudo com o auxílio de modelos como Wavewatch III (Carvalho, 2010;Pianca et al, 2010;Ostritz, 2012;Silva, 2012;Gomes, 2014) e também o TOMAWAC (Oleinik et al, 2016a,b).…”
unclassified